Ecosystem-based adaptation to climate change: What scope for payments for environmental services? - Wertz-Kanounnikoff, Shiela; Locatelli, Bruno; Wunder, Sven; Brockhaus, Maria (2011)
In recent years, there has been a growing interest in payments for environmental services (PES) for ecosystem-based adaptation (EBA). So far, however, experiences and theoretical analyses of PES specifically for adaptation have not been well documented. This paper addresses this gap by analysing the opportunities and constraints of PES as an instrument for EBA. Specifically, we examine the potential for PES to address key elements for adaptation by focusing on three pathways: the user side, the provider side and institutional and societal change. In addition, we assess whether PES fulfils key requirements for adaptation policy instruments, notably effectiveness, efficiency, equity and legitimacy. We find that PES are not a panacea for all environmental services and country contexts, but can be promising adaptation policy instruments where certain preconditions are met and synergies prevail. We conclude on four points especially relevant for the practical scope for PES-adaptation synergies: (i) natural adaptation co-benefits (where the targeted environmental service serves a dual function, e.g. secured water quality and increased adaptive capacity), (ii) piggy-backing (where adaptation benefits are coincidental outcomes), (iii) adaptation-relevant institutional and sectoral spillovers from PES schemes, and (iv) direct payments for adaptation benefits.